The Impact of centralization on democracy in Russia - Pavlova, Aleksandra; Němec, Jan, 1980 srpen 23.-; Cibulková, Petra, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The thesis aims at analyzing the consequences of centralization policies in Russia and its impact on the quality of democracy in the country. Centralization is believed to strengthen states' political power by increasing the effectiveness of governance and proliferation of secession movements. However centralization is also very often associated with antidemocratic governance because it implies the limitation of local authorities' power which can lead to decrease of local official's responsiveness, people participation etc. Thus there should be taken into account many factors when assessing whether the centralization policy is necessary or not.
Vedoucí práce: Jan Němec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses